1995
DOI: 10.2118/27759-pa
|View full text |Cite
|
Sign up to set email alerts
|

Core Acquisition and Analysis for Optimization of the Prudhoe Bay Miscible-Gas Project

Abstract: Summary Core data from a sidetrack well 250 ft from an old injection well showed intervals of excellent miscible-gas sweep, with miscible-flood residual oil saturations (ROS's), Sorm, of ˜5% PV. Less-well-swept intervals had intermediate Sorm values. Numerous intervals had not been contacted by miscible injectant (MI). Chromatographic analyses of the Dean-Stark core extracts quantified miscible-gas alteration of the oil and was especially valuable in the interpretation of intermediate oil sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…When used after a water flood this has the effect of re-establishing a pathway for the remaining oil to flow through and results in a very low residual oil saturation (2% has been measured in reservoir cores recovered from gas swept zones [51]). The drawback of this process is that the gas is both less viscous and less dense than the oil.…”
Section: Overview Of Conventional Enhanced Oil Recovery Processesmentioning
confidence: 99%
“…When used after a water flood this has the effect of re-establishing a pathway for the remaining oil to flow through and results in a very low residual oil saturation (2% has been measured in reservoir cores recovered from gas swept zones [51]). The drawback of this process is that the gas is both less viscous and less dense than the oil.…”
Section: Overview Of Conventional Enhanced Oil Recovery Processesmentioning
confidence: 99%
“…Flow-visualization experiments (Stalkup, 1970;Chatzis et al, 1983;Campbell and Orr, 1985;Bahralolom et al, 1988;Stern, 1991) showed that microscopic oil bypassing was related to pore structures with bimodal or wide pore-size distributions. Shielding of oil by water films in pores can also hinder the contact between the bypassed oil and injection gas in the region with high water saturations (Shelton and Schneider, few inches can cause marked oil bypassing by gas (McGuire et al, 1995). Front instability can also lead to oil bypassing, if the mobility ratio between the injection gas and reservoir oil is large (Gardner and Ypma, 1984;Brock and Orr, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The nonconventional EOR program began in 1996 initially as a MI stimulation (MIST) of an individual well. 4 The program evolved to utilizing a Miscible Injector sidetrack (MIST) to provide a horizontal completion with multiple injection points along the horizontal section of the wellbore (see Figs.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Prior to the start of the PBMGP, continuous and WAG floods were carried out on 16 plugs taken from a total of 4 preserved cores. These cores were injected with different miscible gas compositions and varying quantities of between 0.88 and 3.74 pore volumes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation